Motor Cortex Plasticity in Children With Spastic Cerebral Palsy: A Systematic Review. Issue 4 (4th July 2017) - de Almeida Carvalho Duarte, Natália; Collange Grecco, Luanda André; Zanon, Nelci; Galli, Manuela; Fregni, Felipe; Santos Oliveira, Claudia
ABSTRACT: A review of the literature was performed to answer the following questions: Does motor cortex excitability correlate with motor function? Do motor cortex excitability and cortex activation change after a rehabilitation program that results in improvements in motor outcomes? Can the 10–20 electroencephalography (EEG) system be used to locate the primary motor cortex when employing transcranial direct current stimulation? Is there a bihemispheric imbalance in individuals with cerebral palsy similar to what is observed in stroke survivors? the authors found there is an adaptation in the geometry of motor areas and the cortical representation of movement is variable following a brain lesion. The 10–20 EEG system may not be the best option for locating the primary motor cortex and positioning electrodes for noninvasive brain stimulation in children with cerebral palsy.